RESONANT OSCILLATIONS OF A ROTOR ON AXIALLY PRELOADED BALL BEARINGS UNDER THE JOINT ACTION OF UNBALANCE AND VIBRATION OF SUPPORTS - Filipkovskyi, S.; Makovyey, R.; Филипковский, С. В.; Маковей, Р. Г.; Філіпковський, С. В.; Маковєй, Р. Г. (Харьковский национальный автомобильно-дорожный университет, 2016)
The model of nonlinear vibrations of the rotor supported by axial preload angular ball-bearings was developed. The frequency response of the system is obtained by the continuation method at joint action of unbalance and vibration of supports. Analysis showed that vibrations occurred not only at fundamental resonant frequencies but also at frequencies less than the resonant ones in integer times. The character of periodical decisions is investigated.
РЕЗОНАНСНЫЕ КОЛЕБАНИЯ РОТОРА НА ШАРИКОПОДШИПНИКАХ С ОСЕВЫМ НАТЯГОМ ПРИ СОВМЕСТНОМ ДЕЙСТВИИ ДИСБАЛАНСА И ВИБРАЦИИ ОПОР
РЕЗОНАНСНІ КОЛИВАННЯ РОТОРА НА ШАРИКОПІДШИПНИКАХ З ОСЬОВИМ НАТЯГОМ ПРИ СПІЛЬНІЙ ДІЇ ДИСБАЛАНСУ І ВІБРАЦІЇ ОПОР
Keywords: rotor; angular ball bearing; nonlinear vibrations; resonance; ротор; радиально-упорный шарикоподшипник; нелинейные колебания; резонанс; 534.1